2012
DOI: 10.5114/aoms.2012.32405
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analyses of susceptibility to increased body weight

Abstract: IntroductionObesity is a complex condition with multifactorial origin. Assuming that such a state is genetically controlled, the aim of our study was to evaluate the degree of genetic homozygosity among overweight and obese individuals by the homozygously recessive characteristics (HRC) test.Material and methodsWe analysed the presence, distribution and individual combination of 15 selected genetically controlled recessive phenotype traits in a sample of 140 individuals with increased body mass index (overweig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Despite the numerous population genetic studies previously conducted [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 20 , 21 , 22 ], establishing expected phenotype variations in humans is still a challenging task. Our findings are in line with such statement, since we have demonstrated the presence of differences in such variations between evaluated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous population genetic studies previously conducted [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 20 , 21 , 22 ], establishing expected phenotype variations in humans is still a challenging task. Our findings are in line with such statement, since we have demonstrated the presence of differences in such variations between evaluated groups.…”
Section: Discussionmentioning
confidence: 99%
“…The HRC-test has been developed to establish the proportion of homozygously-recessive clearly-expressed characteristics in every individual as markers of chromosomal homozygosities, implicating the degree of genetic homozygosity in humans [ 8 , 16 , 20 , 21 ]. It is reliable method for estimating the individual homozygosity and is performed by direct observation of defined phenotype traits [ 9 , 10 , 16 , 20 , 21 , 22 ]. To secure the same objectivity and equal criteria for determination of HRCs, one person performed the testing on studied population.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity has a constantly growing prevalence worldwide, and it represents one of the most important health risks of our time [ 40 42 ], so it is recommended that studies that deal with obesity effects on different aspects of health must be continued.…”
Section: Discussionmentioning
confidence: 99%
“…During the thirty years of developing the homozygous recessive characteristics (HRC) test, the authors of the Belgrade population-genetic school selected 15 to 20 as the most reliable characteristics according to the type of inheritance and variability [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. By establishing the extremely expressed recessive phenotypes, they actually gained insight into the status of these gene loci and the general homozygosity of individuals and groups.…”
Section: Introductionmentioning
confidence: 99%
“…These authors studied the distribution and frequency of a series of highly expressed recessive morphophysiological traits in order to estimate individual and group differences (i.e., comparison between ill and healthy individuals, pupils from special and regular schools and carriers of different blood types). Furthermore, previous population genetics studies showed that the number of tested traits was adequate for comparisons of different subpopulation groups [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%